TIPE KESANTUNAN TUTURAN JAWA PADA MASYARAKAT JAWA PESISIR - M. Suryadi (Universitas Muhammadiyah Surakarta, 2012)
Javanese coastal communities have a different form of civility with the standard Java language. This difference is very substantial. Standard Java language still maintains strong normative rules, being at the coast of Java language has undergone a shift. The shift that has occurred: (1) type P_1 (model civility good manners): Speakers have the freedom to use the lexicon of krama or krama inggil for yourself (or good manner self), (2) type P_2 (model civility verbal reduplication): speakers have freedom of speech that has been reiterated by the partners speech. Two shifts are to be taboo for speakers of the standard Java language, and otherwise be inappropriate for polite Javanese coastal communities because of the high frequency of use.